Assessment of Settlement Quality Levels in Balikpapan Kota Subdistrict, Balikpapan, Indonesia - Mega Ulimaz; Reynaldi Yudha Pratama; Ajeng Nugrahaning Dewanti; Elin Diyah Syafitri (Universitas Diponegoro, 2022)
Balikpapan is experiencing rapid urbanization and has an essential role in settlement development. One of the strategic issues of settlements in Balikpapan is the settlements that have decreased in quality in residential in urban areas with a mild level of slum. Based on the Balikpapan Spatial Plan, the spatial pattern in the Balikpapan Kota Subdistrict is dominated by the Settlement Area. It can be said that the components of settlements are the components that are planned to support settlement activities. Therefore, it is necessary to assess the quality of settlements in the Settlement Area in the Balikpapan Kota Subdistrict. The analysis was carried out by quantitative descriptive method (scoring method) with the unit of study for each settlement block or neighborhood. The analysis results of the quality of settlements in the Balikpapan Kota Subdistrict tend to have reasonable quality settlements. There were no areas that had poor settlement quality values. In the research area, from 131 neighborhoods, 19 neighborhoods still have a moderate quality of settlements. It is necessary to increase several components to improve the quality of settlements in each block so that all settlements become more liveable.